CICLODEXTRINAS COMO CARREADORES DE FÁRMACOS PARA SISTEMA NERVOSO CENTRAL VIA MODELAGEM MOLECULAR - Vendrame, Laura Fernanda Osmari Vendrame (2019)
In this thesis, the study of cyclodextrin (CDs), as a carrier for the Central Nervous System (CNS) is studied through quantum initiation calculations, molecular docking and molecular dynamics. The chemotherapeutic methotrexate is also studied, with its CD complex being evaluated, as well as receptor-ligand studies with the P-glycoprotein due to its ability to expel drugs from the CNS. Methotrexate is hydrophilic and anticancer, widely used in CNS neoplasms. However, its low permeability in the blood / brain barrier and high toxicity make further studies for the use of this drug important. The association of this chemotherapeutic with nanostructures such as cyclodextrins (CDs) and the P-glycoprotein is an important study that aims to contribute to studies to increase its delivery in the CNS and decrease its toxic effects. At first, it's presented in this work the results in DFT which are promissing in regards of MTX-CD delivery to the NCS, since we want the drug to be in the cyclodextrin cavity due to its hydrophobic interior and hydrophilic exterior without occurring covalent bonds that change the drug's active principle making it difficult to release at the target site. Second, the study of molecular docking in the present work on CDs with P-glycoprotein may open the way for the use of CDs in studies for the CNS to make regulatory decisions on drug delivery, allowing the prediction of potential impacts on treatments for the CNS. Finally, the work done with the GROMACS program constitutes a benchmark for future studies based on the GROMOS force field, suggesting its potential for MTX and condensed-phase β-CD studies. It also opens the perspective of the use of new techniques of molecular and metadynamic dynamics, with these parameters, in the study of the conformational profile, dynamics and flexibility of drugs in solution.